The Effect of Organizational Culture and Leadership on Employee Performance with Work Motivation as an Intervening Variable at PT PLN Pusdiklat Ragunan Jakarta - Pabi, Nurdin; Nur Aktif Budiono (Dinasti Publisher, 2023)
The main objective of this study is to examine how organizational culture, leadership, and work motivation influence the performance of employees at the Training Center of PLN Ragunan Jakarta. The research population comprised employees of the Training Center at PLN Ragunan Jakarta, with a total sample size of 93 individuals. The data analysis method employed was SEM-PLS. The findings revealed that organizational culture has a positive impact on employees' work motivation, and similarly, leadership also positively affects employees' work motivation. Additionally, both organizational culture and leadership have a positive influence on employee performance. Furthermore, work motivation positively influences employee performance. The study also established that organizational culture indirectly affects employee performance through work motivation, and similarly, leadership indirectly affects employee performance through work motivation.